2015
DOI: 10.1186/s40623-015-0360-6
|View full text |Cite
|
Sign up to set email alerts
|

IMF-By dependence of transient ionospheric flow perturbation associated with sudden impulses: SuperDARN observations

Abstract: A statistical study using a large dataset of Super Dual Auroral Radar Network (SuperDARN) observations is conducted for transient ionospheric plasma flows associated with sudden impulses (SI) recorded on ground magnetic field. The global structure of twin vortex-like ionospheric flows is found to be consistent with the twin vortices of ionospheric Hall current deduced by the past geomagnetic field observations. An interesting feature, which is focused on in this study, is that the flow structures show a dawn-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Effects of the passage of TCVs are also seen at mid-latitudes in ground scatter returns, as shown by Kim et al (2012). Meanwhile, Hori et al (2015) demonstrated using the high-and mid-latitude SuperDARN data that there is a dawn-dusk asymmetry of flow vortices as shown in statistical convection velocity perturbations, caused by IMF By polarity, which appears associated with negative SI events (dynamic pressure decrease) that is not seen for positive SI events. However, most of the observations were poleward of 60°M LAT, and all measurements were considered not just those associated with TCVs.…”
Section: Transientsmentioning
confidence: 89%
“…Effects of the passage of TCVs are also seen at mid-latitudes in ground scatter returns, as shown by Kim et al (2012). Meanwhile, Hori et al (2015) demonstrated using the high-and mid-latitude SuperDARN data that there is a dawn-dusk asymmetry of flow vortices as shown in statistical convection velocity perturbations, caused by IMF By polarity, which appears associated with negative SI events (dynamic pressure decrease) that is not seen for positive SI events. However, most of the observations were poleward of 60°M LAT, and all measurements were considered not just those associated with TCVs.…”
Section: Transientsmentioning
confidence: 89%
“…J C connects with J MP to form a current loop. Due to the enhanced current within this loop, the vertical component of the Earth’s magnetic field increases (by a factor b in Figure 1a); this results in a well observed rapid positive increase in SYM‐H (e.g., Hori et al., 2015; Takeuchi et al., 2002).…”
Section: Introductionmentioning
confidence: 90%
“…Hori et al. (2015) define the SC signature in SYM‐H as an increase of more than 5 nT with a gradient greater than about 15 nT per 10 s. Given the magnitude of the pressure change, SIs can have a remarkably dramatic impact on the Earth’s magnetosphere, and the electrodynamics within.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present study further confirms the penetration of dawn-to-dusk convection electric field to equatorial altitudes in response to sudden enhancements in solar wind density alone without any significant changes in the velocity and IEFy. Further, this study also showcases the PPEFs of opposite polarity in response to sharp reduction in the density, probably due to sudden reduction in convection electric fields in order to adjust for the rarefied state of magnetosphere (Araki & Nagano, 1988;Hori et al, 2015).…”
Section: 1029/2020ja027869mentioning
confidence: 56%